A Comparison Between Fama and French Model and Liquidity-Based Three Factor Models in Predicting Portfolio Returns - Ruzita Abdul Rahim; Abu Hassan Shaari Mohd. Nor (Asian Academy of Management Journal of Accounting and Finance, 2006)
The main objective of this paper is to evaluate the forecasting accuracy of two liquidity-based three-factor models, SiLiq and DiLiq, which have been developed as potential improvements on the Fama-French model. Using common stocks of 230 to 480 listed firms, this study constructs 27 test portfolios double-sorted on: (i) size and book-to-market ratio (B/M), (ii) size and share turnover (TURN) and (iii) B/M and TURN. The study sets the periods of January 1987 to December 2000 for estimation and January 2001 to December 2004 as forecast sample. The forecast errors are measured using mean absolute percentage errors and Theil's Inequality Coefficient. The preliminary results clearly document that three-factor models outperform CAPM. While the hypotheses of no significant differences cannot be rejected, the marginal difference in the errors of the competing three-factor models indicate that predicting returns on stocks traded on Bursa Malaysia can be slightly improved by incorporating illiquidity risk in a three-factor model in the form of DiLiq.